A Prototype of High Rise Residential Management Systems in Malaysia: A Case Study for Seroja Apartment - Nuha, Hilyatun; Wati, Putu Eka Dewi Karunia; Mokhsin, Mudiana; Shahuddin, Ahmad Zambri; Zainol, Amer Shakir; Mohd Som, Mohd Husni; Binti Hazemi, Nurhaziani (School of Industrial and System Engineering, Telkom University, 2020)
Residential high-rises are unique properties that differ from landed properties such as bungalows or terrace houses. They are unique insofar as, after the properties have been occupied, facilities must be jointly managed by residents. The continuous growth of high-rise residential buildings specifies that there is a need for effective ownership and property management system to instill a valuable living experience among high-rise residents in this country. Looking at this scenario, this research takes an initiative to develop a mobile application that supports streamline information with assistive features to improve communication and information sharing for high-rise residential management in Malaysia. This aim is achieved by answering three research objectives, including identifying user requirements, designing the application prototype and developing the artefact and evaluating the artefact. The study was conducted together with LT Sdn Bhd, the property management company responsible in managing and maintaining property related matters of Seroja Apartment. An adopted conceptual framework for property management based on the sustainable indicator dimensions for property management and applicable features from existing mobile application to develop the artefact has been proposed. The conceptual framework was proposed based on literature review and nature of work observed on site. Lastly, the study successfully validated the proposed adopted framework against the artefact, the MyLT mobile application.